Revolutionizing College English Reading with ChatGPT: Current Predicaments and Future Directions - Li, Wanfen; Tang, Yaru; Wang, Siyu (Transactions on Social Science, Education and Humanities Research, 2024)
With the acceleration of globalization, foreign language education in colleges and universities has been paid more and more attention. Combined with the development of artificial intelligence, ChatGPT is also widely used in the educational sector. In the future of technology-facilitated education, it will be more closely integrated with foreign language education to create better teaching activities for teachers and students. This paper aims to analyze the necessity of ChatGPT joining the college English reading teaching module through the shortage of educational resources and the dilemma of teaching mode. This paper also clarifies its possible advantages and disadvantages, as well as the corresponding use of various characteristics of the teaching scene. It examines the relationship between this artificial intelligence tool and the two parties, namely teachers and students, and the definition of their roles. The final conclusion of this paper is expected to lead the public to have a deeper understanding of ChatGPT, or to alert users to cautiously and correctly view the role of AI tools in the teaching and learning domain.